Post a New Question

Algebra1

posted by on .

i think i have to simplify.... but the question just says:
(2y-3)^2
possible answers:
a.4y^2+9
b.4y^2-6y+9
c.4y^2-12y+9
d.4y^2+12y+9

  • Algebra1 - ,

    separate and multiply based on

    FOIL
    first
    outer
    inner
    last
    (2y-3)^2=

    (2y-3)(2y-3) then use foil and multiply the first term, outer term, inner terms then last terms .

    (2y-3)(2y-3)

    first terms multiplied

    2y*2y= 4y^2

    outer terms multiplied

    2y*(-3)=-6y

    inner terms multiplied

    (-2y)*3=-6y

    last terms multiplied

    (-3)*(-3)=9

    Now combined FOIL (first outer inner and last terms )

    4y^2-6y-6y+9= but now you can combine the -6y's so (-6y-6y=-12y)

    and you get 4y^2-12y+9

  • Algebra1 - ,

    thank you...

  • Algebra1 - ,

    Your welcome =)

  • Algebra1 - ,

    duplicate post

  • Algebra1 - ,

    inner terms multiplied

    2y*(-3)=-6y

    it is the same as the outer terms multiplied (the negative was misplaced before)

  • Algebra1 - ,

    Oh..it was a duplicate?
    Oh well I solved it Dr.Bob.=D
    anyways..ha

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question